Identification of animal species in rendering products by dna technology - Ercan Kurar; Yusuf Özşensoy; Müge Doğan Bülbül; Mehmet Nizamlıoğlu (Eurasian Journal of Veterinary Sciences)
After bovine spongiform encephalopathy (BSE) outbreak, the use of especially ruminant byproducts in animal rations is under strict control. An animal feedstuff sample was sent from the Turkish Republic, Mersin Customs Directorate in order to identify the animal source. The feedstuff was declared as “hydrolyzed feather meal” in the custom declaration and health certificates. In microscopic inspections, pieces of feathers and hollow shafts were observed. As an alternative method, DNA was extracted by using standard phenol/chloroform and dodecyltrimethylammonium bromide (DTAB) methods. The DNA samples were amplified by Polymerase Chain Reactions (PCR) using poultry, ruminant, swine, horse and carnivore specific oligos. In PCR reactions, chicken, goat, horse and cat DNAs were used as positive controls. DNA free PCR reactions were also amplified as negative control in each system. The resulting PCR products were separated and visualized by electrophoresis on a 2% agarose gel. The findings suggested presence of poultry DNA in the feedstuff sample since two different poultry specific PCR primer pairs resulted in positive PCR products. However, no PCR products were observed in ruminant, swine, horse and carnivore PCR reactions. The results of this study thereby indicated that molecular biology techniques could successfully be used to identify source of heat proceeded animal byproducts.